Some aspects of green building in Poland in the context of systems for certification of ecological buildings - Lewandowska, Aleksandra; Rogatka, Krzysztof; Wylon, Mirosław (Studia Ecologiae et Bioethicae, 2019)
The goal of the paper is to explain special character and evaluate green building in Poland in the context of ecological building application process. The author tries to define social and economic factors contributing to development of this type of building in Poland. The paper also describes spatial variety in voivodeship scale in reference to localization of buildings with ecological certificate and points out green building structure in Poland. To complete the task, the author uses mainly the data from Polish Green Building Council. The work clearly indicates raise in number of certificates of ecological building, what evidences development of this type of building. We also observe spatial variety of green building in the country scale (most of these buildings are located in big cities of Poland).